A&T Gujarat Implementation Research Baseline Survey 2022: Women with Children - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
This dataset originates from the survey of women with children under 2 years, conducted as part of the baseline for the impact evaluation of the Alive & Thrive (A&T) project in Gujarat, India. The survey was designed to assess the effectiveness of systems-strengthening interventions and local governance engagement in improving the quality and co-coverage of health and nutrition services during the first 1,000 days of life.